Psychological Safety in the Workplace: Fostering Open Communication and Innovation - Mahdia, Asrini (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Psychological safety in the workplace is of key importance in influencing individual well-being, team performance, and an organization's ability to innovate. This research aims to investigate the relationship between psychological safety at work and organizational innovation, as well as its managerial implications. This research method uses the PRISMA method to collect and analyze articles from international databases such as Scopus and Web of Science. The selected articles include empirical studies that explore the relationship between psychological safety and organizational innovation. The research results show that psychological safety plays a crucial role in facilitating an environment where employees feel safe to collaborate, take risks, and convey new ideas without fear of negative judgment. The implications of these findings highlight the importance of developing organizational policies that support psychological safety to enhance innovation and organizational performance.